Exploration of Climate Change Awareness among Students at a South African Public University - Uwizeyimana, DE; Sekgobela, C (International Journal of Social Science Research and Review, 2023)
This study aimed to explore climate change awareness among students at a South African public university. The quantitative research method was applied in this study. Due to Covid-19 protocol requirements, a semi-structured electronic questionnaire was used to collect data from students at one South African public university whose name is withheld due to confidentiality requirements. One of the main findings of this study is that most respondents from this particular South African public university are aware that climate change is indeed happening. However, most participants in this research needed to be made aware of the international conventions that deal with climate change or climate change. These findings call for intensifying climate change awareness among South African university students across all media outlets. The study recommends that climate change and climate change awareness and combatting strategies be part and parcel of social and economic development programmes at local, national, continental, and global levels. It is vital to ensure that all citizens in general, as well as university students who are likely to be future leaders of communities and countries, have access to scientifically proven evidence on climate change and its impacts from reliable sources, some of which are highlighted in this study.
Keywords: _z:class:countries